BMPR2 promoter variants effect gene expression in pulmonary arterial hypertension patients - Song, Jie; Hinderhofer, Katrin; Kaufmann, Lilian; Benjamin, Nicola; Fischer, Christine; Grünig, Ekkehard; Eichstaedt, Christina (Genes, 2020)
Pathogenic variants have been identified in 85% of heritable pulmonary arterial hypertension (PAH) patients. These variants were mainly located in the bone morphogenetic protein receptor 2 (BMPR2) gene. However, the penetrance of BMPR2 variants was reduced leading to a disease manifestation in only 30% of carriers. In these PAH patients, further modifiers such as additional pathogenic BMPR2 promoter variants could contribute to disease manifestation. Therefore, the aim of this study was to identify BMPR2 promoter variants in PAH patients and to analyze their transcriptional effect on gene expression and disease manifestation. BMPR2 promoter variants were identified in PAH patients and cloned into plasmids. These were transfected into human pulmonary artery smooth muscle cells to determine their respective transcriptional activity. Nine different BMPR2 promoter variants were identified in seven PAH families and three idiopathic PAH patients. Seven of the variants (c.-575A>T, c.-586dupT, c.-910C>T, c.-930_-928dupGGC, c.-933_-928dupGGCGGC, c.-930_-928delGGC and c.-1141C>T) led to a significantly decreased transcriptional activity. This study identified novel BMPR2 promoter variants which may affect BMPR2 gene expression in PAH patients. They could contribute to disease manifestations at least in some families. Further studies are needed to investigate the frequency of BMPR2 promoter variants and their impact on penetrance and disease manifestation.
Gesehen am 24.11.2020